Limited and Limiting Conversations about the Poor: Elizabethan Prescriptions to Poverty in the Canadian Press - Harding, Robert (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
I In recent years, globalization has gone hand in hand with government de-regulation, resulting in an erosion of the hard-won social contract between Canadians and their government. Canadians have witnessed the dismantling of the welfare state and a gradual decline in social entitlements. Homelessness and food bank use have dramatically increased, while income security and minimum wage rates have steadily eroded due to inflation. This study of 193 news texts about poverty published in 13 Canadian newspapers in 2012 found evidence of the prominence of established and emerging poverty discourses that blame poor people for their plight or cast them in a negative light. Keywords: Poverty; inequality; content analysis; critical discourse analysis; media Résumé Ces dernières années, la mondialisation est allée de pair avec la dérèglementation gouvernementale, entrainant une érosion du contrat social, durement acquis, entre les Canadiens et Canadiennes et leur gouvernement. Le peuple canadien a assisté au démantèlement de l'État providence, et le déclin graduel des droits sociaux. L'itinérance et l'utilisation des banques alimentaires ont augmenté de façon spectaculaire, en même temps que la sécurité du revenu et les taux du salaire minimum ont graduellement érodé en raison de l'inflation. Cette étude de 193 textes des nouvelles sur la pauvreté, publiés dans 13 journaux canadiens en 2012 a permis d'établir l'importance de discours, établis et émergent, sur la pauvreté, qui blâme les personnes pauvres pour leur situation, ou qui les présentent dans un optique négatif. Mots clés: Pauvreté; inégalité; analyse de contenu; analyse critique du discours; média